Farmers Social Movement Studies: A Systematic Literature Review for A Conceptual Model - Wahyudi Wahyudi (Universitas Muhammadiyah Tangerang, 2021)
This research aims to formulate a conceptual model of farmers' social movement based on previous studies, which failed to explain this concept. The Systematic Literature Review (SLR) method with a mixture of qualitative and quantitative approaches was used to conduct this research. Data were obtained from 289 articles sourced from the Scopus Database, with the VOSVIEWER and NVIVO 12 software used to determine the conceptual model. The analysis results showed that this study is associated with farmers’ issues, agricultural governance, agricultural systems, and the collaboration of stakeholders in managing agricultural production. These perspectives are used to explain the concepts, topics, and issues of the farmer's social movement, including the role of actors, dynamics of conflict, challenges, and struggles of the movement, processes, conservation, sustainable environment, cooperation, the collaboration of stakeholders, as well as production and marketing of agricultural products. This conceptual model contributes to the development of farmers' social movement studies oriented towards concept development and disclosing issues in the field. Paper ini bertujuan untuk memformulasikan konseptual model studi gerakan sosial petani berdasarkan pada penelitian terdahulu. Metode yang digunakan pada penelitian ini adalah metode Systematic Literature Review (SLR) dengan pendekatan campuran kualitatif dan kuantitatif. Pendekatan SLR digunakan untuk mereview 289 artikel yang bersumber dari Scopus Database.Review paper menggunakan software VOSVIEWER dan NVIVO 12 yang menghasilkan data untuk menjawab pertanyaan penelitian, yaitu bagaimana model konseptual studi gerakan sosial petani.Hasil analisis dengan SLR mengungkapkan bahwa studi gerakan sosial petani berkaitan dengan isu-isu gerakan petani, tata kelola pertanian, sistem pertanian, dan kolaborasi stakeholders dalam mengelola produksi pertanian, yang dijelaskan melalui perspektif sosiologi, ilmu lingkungan, dan manajemen pertanian. Perspektif tersebut digunakan untuk menjelaskan konsep, topik, dan isu-isu gerakan sosial petani, meliputi peran aktor, dinamika konflik, tantangan dan perjuangan gerakan, proses gerakan, konservasi, lingkungan berkelanjutan, kerjasama, kolaborasi stakeholders, dan produksi serta pemasaran hasil pertanian. Model konseptual tersebut berkontribusi terhadap pengembangan studi gerakan sosial petani, baik berorientasi pada pengembangan konsep maupun pengungkapan isu-isu gerakan sosial petani yang berlangsung di lapangan.